2006
DOI: 10.1590/s1516-35982006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de fatores de ambiente e estimativas de parâmetros genéticos para a característica dias para o parto na raça Nelore

Abstract: RESUMO -Dados de um rebanho comercial da raça Nelore foram analisados com os objetivos de avaliar a influência de fatores ambientais e estimar parâmetros genéticos para a característica dias para o parto (DPP). Foram utilizados modelos fixos que incluíram os efeitos de grupo de contemporâneos, sexo do bezerro, idade da vaca no início da estação de monta, mês do parto anterior e peso do bezerro desmamado no final da estação de monta (apenas este último efeito não influenciou a característica significativamente)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the present study, the DC trait was only analysed in females that calved. Forni & Albuquerque (2006) performed analyses considering only females that calved and including all females exposed to bulls, even those with no calving record, with a penalty being attributed to animals that did not calve, that is, 21 days was added to the highest value found for the management group. The authors observed no genetic differences between animals when the data of all exposed females were included, attributing a penalty to those with no calving record.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the DC trait was only analysed in females that calved. Forni & Albuquerque (2006) performed analyses considering only females that calved and including all females exposed to bulls, even those with no calving record, with a penalty being attributed to animals that did not calve, that is, 21 days was added to the highest value found for the management group. The authors observed no genetic differences between animals when the data of all exposed females were included, attributing a penalty to those with no calving record.…”
Section: Resultsmentioning
confidence: 99%
“…Em consonância, a melhoria dos índices de precocidade sexual possibilita a redução do tempo ocioso dos animais e o aumento do número de bezerros produzidos ao longo da vida útil da vaca. Já características como STAY, indicadora da longevidade reprodutiva, possibilitam a ampliação do descarte voluntário e diminuição dos custos com alimentação com fêmeas improdutivas (17), (18),( 14), (16) .…”
Section: Introductionunclassified
“…Improvement of sexual precocity makes it possible to reduce the animals' pre-productive time and increase the number of calves produced in the cow's lifetime. On the other hand, improvement of STAY, an indicator of reproductive longevity, make it possible to reduce feeding costs with unproductive females (17), (18), (14), (16) .…”
Section: Introductionmentioning
confidence: 99%